Improving Resistance of Gravity Dam to Seismic Wave by Using Stepped Base - Jabbar Asmaa Abdul (EDP Sciences, 2021)
This study analyzes the possible modes of the seismic wave for concrete gravity dams and the damage occurring in the body where two gravity dam sections are taken as a case study. Model (1) is a typical section of a gravity dam, while model (2) is a gravity dam section provided with specified steps at its base. The design of seismic waves included Operational Base Earthquake (OBE), Maximum Design Earthquake (MDE), and Maximum Credible Earthquake (MCE) levels. The dam body-foundation-reservoir water interaction system is analyzed by numerical analysis software (ABAQUS). The main conclusion shows that the gravity dam model's underground motion loadings have a noticeable increase in the displacement distribution within the first gravity dam body model, especially in the higher mode compared to the first model. The first model's Damage Index value was equal to 0.357 at the MCE wave, which does not appear in the second model. The time taken for the damage that occurs within a model (1) is faster than the model (2). Consequently, model (2) significantly reduces seismic waves with different intensity levels on the amount of damage transmission within the gravity dam body.